Membangun SDM Berkarakter Melalui Kurikulum Madrasah Menuju Generasi Emas 2045 - Sinulingga, Neng Nurcahyati; Dalimunthe, Amsal Qori (Tarbawiyah Jurnal Ilmiah Pendidikan, 2024)
This study aims to analyze the role of the madrasa curriculum in building human resources (HR) with character, to prepare the Golden Generation in 2045. Using the literature study method, this research examines various relevant sources, including reputable journals, books, and education policy documents. The findings reveal: (1) the madrasa curriculum shapes character and competence through intracurricular and extracurricular activities, Pancasila student profiles, local content, and project-based learning; (2) challenges in developing the curriculum include internal issues such as suboptimal implementation of eight standards, limited HR in Islamic educational institutions, and the impact of technological changes on character education, leading to moral degradation, and external challenges such as future demands, societal views, and technological advancements; (3) effective strategies for implementing a character-building curriculum involve creating a competitive approach that integrates general and Islamic education, and developing religious education strategies both inside and outside the madrasah.